Implementation of the Emergency Curriculum and Its Impact on Student Competency Achievement at SDN Pameungpeuk, Cisarua, Bandung Regency - M. Yusuf Sanny; Ratnanto Aditiarno; Candra Mecca Sufyana (Jurnal Pendidikan dan Kebudayaan Nusantara, 2026)
Curriculum implementation is a key factor in achieving students' expected learning competencies. Although the Curriculum for Special Conditions has been implemented to provide greater flexibility in learning, empirical evidence regarding its implementation at the elementary school level and its contribution to student competency achievement remains limited. This study aimed to analyze the implementation of the Curriculum for Special Conditions and its contribution to student competency achievement at SDN Pameungpeuk, Cisarua, West Bandung Regency, Indonesia. A descriptive qualitative approach was employed involving the principal, the vice principal for curriculum affairs, and teachers as research participants. Data were collected through interviews, observations, and document analysis and were analyzed using descriptive qualitative techniques. The findings indicate that the curriculum was implemented through systematic planning, learning implementation, and evaluation processes. Teachers were able to prioritize essential learning competencies while adapting instructional strategies to students' learning needs, thereby supporting the achievement of the expected competencies. The novelty of this study lies in providing empirical evidence on the implementation of the Curriculum for Special Conditions at the elementary school level and demonstrating its contribution to competency-based learning practices that support student achievement.